2017
DOI: 10.1155/2017/3095425
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of T Cell Subsets in Adult Primary/Idiopathic Minimal Change Disease: A Pilot Study

Abstract: Aim To characterise infiltrating T cells in kidneys and circulating lymphocyte subsets of adult patients with primary/idiopathic minimal change disease. Methods In a cohort of 9 adult patients with primary/idiopathic minimal change recruited consecutively at disease onset, we characterized (1) infiltrating immune cells in the kidneys using immunohistochemistry and (2) circulating lymphocyte subsets using flow cytometry. As an exploratory analysis, association of the numbers and percentages of both kidney-infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Currently, minimal change disease (MCD) is believed to be due to podocyte damaged by glomerular permeability factors produced from abnormal T-lymphocyte subsets ( 37 , 38 ). Another study found that CD4 + T cells in patients with relapsed MCD were significantly upregulated ( 39 ), further confirming the role of T cells in the development of this condition. Thus, the occurrence of kidney diseases is related to the immune environment, especially the number and function of T-lymphocytes.…”
Section: Discussionmentioning
confidence: 75%
“…Currently, minimal change disease (MCD) is believed to be due to podocyte damaged by glomerular permeability factors produced from abnormal T-lymphocyte subsets ( 37 , 38 ). Another study found that CD4 + T cells in patients with relapsed MCD were significantly upregulated ( 39 ), further confirming the role of T cells in the development of this condition. Thus, the occurrence of kidney diseases is related to the immune environment, especially the number and function of T-lymphocytes.…”
Section: Discussionmentioning
confidence: 75%
“…35 However, a recent study in adults with new onset idiopathic MCD showed no significant difference in the percentage of CD4 + and CD8 + T cells compared with controls. 36 In our cohort of SDNS patients, the percentage of CD4 + memory T cells was significantly higher in both MCD and FSGS compared with controls, excluding it as a useful marker to differentiate between MCD and FSGS in our patients with SDNS.…”
Section: Discussionmentioning
confidence: 58%
“…However, not much is known about which type of T cell subset and cytokine play a critical role in the pathogenesis of MCD. Previous studies revealed that patients with MCD were characterized by downregulation of Th1 cytokines and predominance of Th2 and Th17, which might be harmful factors of glomerulus, leading to the occurrence and development of MCD (Le Berre et al, 2005;Salcido-Ochoa et al, 2017). However, Kaneko et al (2002) reported that the percentages of Th1, Th2 and the ratio of Th1/Th2 showed no significant differences between nephrotic relapse, remission and healthy controls in childhood.…”
Section: Introductionmentioning
confidence: 97%